Protection of the Rights of Indigenous Peoples in Natural Resources Management - Basman; Ahsan; Amirullah; Mukhlis Achmad; Muh. Sabir (Pustaka Digital Indonesia, 2026)
The protection of indigenous peoples’ rights in the management of natural resources has become a crucial issue in environmental and agrarian law in Indonesia, particularly in the context of increasing pressure from large-scale natural resource exploitation. Indigenous communities possess a long-standing relationship with their customary territories and natural resources, which is reflected in traditional management systems based on local wisdom, cultural values, and sustainable environmental practices. These systems have contributed significantly to the preservation of ecosystems and biodiversity. However, in practice, the rights of indigenous peoples are frequently marginalized due to overlapping regulations, weak legal recognition, limited participation in decision-making processes, and the expansion of extractive industries and development projects. This study aims to analyze the legal protection afforded to indigenous peoples in the management of natural resources and to evaluate the effectiveness of its implementation within the existing legal framework. The research employs a normative juridical method using statutory and conceptual approaches to examine relevant constitutional provisions, legislation, and legal doctrines. The findings indicate that legal protection has been formally recognized under the 1945 Constitution of the Republic of Indonesia and Law Number 32 of 2009 on Environmental Protection and Management. Nevertheless, its practical implementation remains constrained by inconsistent law enforcement, institutional weaknesses, and conflicts over land and resource tenure. Therefore, stronger legal recognition, effective law enforcement, and inclusive governance are essential to ensure the protection of indigenous peoples’ rights while promoting equitable and sustainable natural resource management.